UPAYA MENINGKATAN HASIL BELAJAR SISWA PADA MATERI ARITMATIKA SOSIAL DENGAN MODEL PEMBELAJARAN RECIPROCAL TEACHING - Hidayati, Nisa Nurul (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
This research is based on the students' low understanding of Social Aritmatics material. Social Arithmetic is an important mathematical material to be mastered by SMP/MTs students. Based on the results of observations made by researchers at SMPN 12 Tarakan, it shows that the Social Arithmetic material taught is still having difficulties and learning outcomes are not optimal. The solution that the researcher will do is to use a reciprocal teaching learning model. The reciprocal teaching learning model has four strategies, namely: summarizing/summarizing, asking questions and solving them, explaining and predicting. This study aims to determine the teacher's ability to manage learning, student activities during learning and student learning outcomes with the reciprocal teaching learning model. The type of research used is Classroom Action Research (CAR) with three cycles in each cycle there are two meetings consisting of planning, action, observation and reflection. The subjects in this study were grade VII students consisting of 32 students. The data was collected by using the teacher's ability observation sheet in managing learning, student activity observation sheets during learning and post-test. Data analysis techniques, researchers used descriptive analysis (percentage) in accordance with the effectiveness criteria that have been determined. The results of this study indicate that in the first cycle, classical student learning outcomes have not reached completeness, namely 34.3%. In the second cycle, classical student completeness is included in the complete category with a percentage of 67.25% and in the third cycle completeness is 81%. The data on the teacher's ability to manage learning is categorized as very good, student activities during learning are generally active. Based on this, it can be concluded that student learning outcomes in Social Arithmetic material increase by using the reciprocal teaching learning model.